PENGETAHUAN IBU HAMIL TENTANG TATALAKSANA INISIASI MENYUSUI DINI - Maharani; Sri Legawati (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Early Breastfeeding Initiation (IMD) is a group that helps new mothers start breastfeeding their babies immediately after birth, usually on the same day. This study aimed to determine community knowledge about how to initiate breastfeeding early at the Firda Hasanah Clinic in Guntung Village, Tanjung Tiram District. This research methodology uses a descriptive survey method and is cross-sectional in nature, with data. Although there were 36 respondents, the sample was determined using a sampling technique known as "sampling determination technique," which states that every time we use an entire group of people or objects as a sample, it occurs when the group is quite small. Not as high as thirty people, and the sample size in this study was a minimum of thirty-six pregnant women who participated in pregnancy at the Firda Hasanah Clinic. The research findings regarding pregnant women's understanding of the implementation of initiation management at the Firda Hasanah clinic, Guntung Village, Tanjung Tiram District can be categorized as "Quite Good" with a percentage of 63.6%. The goal of the Pregnant Women's program is to help students understand the importance of early breastfeeding initiation, starting with themselves, as well as with their friends and family, so that early breastfeeding can be as effective as possible during the most crucial period, the first hour after birth. If the diet plan is successful, strict infant feeding for six months can also be successful, so that the baby receives the best nutrition from the mother.